What Every Client Wants? (Re)mapping the Trajectory of Client Expectations Research - Downie, Jonathan (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2015)
Since the late 1980s, scholars have sought to understand what it is that speakers, audience members or conference organisers want from the interpreters with whom they work. The aim of this paper is to provide a critical review of the work that has taken place to understand these expectations, with a view to fostering a greater understanding of both the expectations of clients and how these expectations could be explored in a more nuanced fashion. Unlike Kurz (2001), who chose to provide an author-centred summary, publications are examined in this paper in chronological order, allowing the historical development of this area of research to be clearly seen. This structure also draws attention to the relative reduction in the number of publications on client expectations published in the first decade of the current millennium. This paper gives possible reasons for this reduction in publication frequency, followed by a detailed exploration of how more recent publications in this area differ from those published in earlier periods. These differences, and most notably the move towards dividing expectations into different categories, representing stereotypical and event-specific requirements of interpreters, are presented as offering a valuable starting point for future research.